Deployment of Negative Emissions Technologies at the National Level: A Need for Holistic Feasibility Assessments - Thoni, Terese; Beck, Silke; Borchers, Malgorzata; Förster, Johannes; Görl, Knut; Hahn, Alena; Mengis, Nadine; Stevenson, Angela; Thrän, Daniela (Frontiers in Climate, 2020)
The 2015 Paris Agreement aims to strengthen the global response to climate change, and to maintain an average global temperature well below 2 °C, with aspirations towards 1.5 °C, by means of balancing sources and sinks of greenhouse gas emissions. Following this, the importance of carbon dioxide removal in global emission pathways has been further emphasized, and Negative Emissions Technologies (NETs) that capture carbon from the atmosphere and remove it from the system have been put in the spotlight. NETs range from innovative, engineered technologies, to well-known approaches like afforestation/reforestation. These technologies essentially compensate for a shrinking carbon budget coupled with hard-to-abate future emissions, and a historical lack of action. However, none has been deployed at scales close to what is envisioned in emission pathways in line with the Paris Agreement goals. To understand the potential contribution of NETs to meet global emission goals, we need to better understand opportunities and constraints for deploying NETs on a national level. We examine 17 Long-Term Low Greenhouse Gas Emission Development Strategies (LT-LEDS), and discuss them in the context of available NETs feasibility assessments. Our mapping shows that most countries include NETs in their long-term strategies, and that enhancement of natural sinks is the most dominating type of NET in these strategies. In line with many feasibility assessments, LT-LEDS focus on technical and biophysical considerations, and neglect socio-cultural dimensions. We suggest that feasibility assessments at the national level need to be more holistic; context-specific and comprehensive in terms of aspects assessed.